Curie Point Depth Analysis of Lesugolo Area, East Nusa Tenggara, Indonesia Based on Ground Magnetic Data - Alamta Singarimbun; Umar Said; Dini Andriani; R. B. Astro; Bakrun Bakrun; I G. P. F. Soerya Djaja; Eleonora Agustine; Pepen Supendi; Wahyu Srigutomo (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
The Curie point depth, or magnetic basal depth, of the Lesugolo geothermal area in Ende, Flores Island, East Nusa Tenggara, Indonesia was estimated by performing spectral analysis on spatial magnetic data and transforming it into the frequency domain, resulting in a link between the 2D spectrum of magnetic anomalies and the depths of the top and centroid of the magnetic sources. Shallow Curie point depths of 16 to 18 km were found in the north-northeast to southeast areas of Lesugolo, while deeper depths of 24 to 26 km were found in the southwest. The tectonic setting beneath the central part of Flores Island governs the distribution of the Curie point depths in the area. Shallow Curie point depth zones are associated with high thermal gradients (30 to 34 °C/km) and heat flow (80 to 100 mW/m2). Deep depths, on the other hand, correspond to zones of low thermal gradient (21 to 26 °C/km) and low heat flow (65 to 80 mW/m2). Both the derived thermal gradient and the heat flow maps contribute to a better understanding of the Lesugolo geothermal system’s configuration. This study suggests that the Lesugolo geothermal area’s prospect zone is located in the center of the investigated area, where the Lesugolo normal fault forms its southeastern boundary.